Lymphangiogram of a case of presumed lymphatic filariasis with left-sided cisterna chyli - Siu Fung Mak, MBBS, FRCR; Kar Ho Lee, MBChB, FRCR, FHKCR, FHKAM; Hing Yan Danny Cho, MBBS, FRCR, FHKCR, FHKAM (Radiology Case Reports)
Lymphatic filariasis is an uncommon condition in Hong Kong and is currently considered as one of the neglected tropical diseases by the World Health Organization. Blood tests are available for diagnosis of acute infections, but false negative results can occur with chronic manifestations of lymphatic filariasis. We present a case which illustrates how radiological imaging can help with diagnosis of lymphatic filariasis.